IBM e server pSeries Cluster systems handbook - Quintero, Dino (IBM, International Technical Support Organization, 2003)
The IBM eServer Cluster 1600 server, which was introduced to meet the rigorous demands of mission-critical enterprise applications, continues to offer outstanding performance, scalability, reliability, availability, serviceability, and management capabilities. In this IBM Redbooks publication, we highlight the benefits of using a Cluster 1600, and describe which hardware components can be managed by either Parallel System Support Programs (PSSP) Version 3, Release 5, or Cluster Systems Management (CSM) Version 1, Release 3, Modification 2. This publication contains the following information on the Cluster 1600: - Cluster 1600 hardware components - Networking components and considerations - Cluster 1600 software components - Scalability of the Cluster 1600 - Solutions and offerings scenarios The Cluster 1600 helps to reduce the complexities and costs of system management, thus lowering the total cost of ownership and allowing simplification of application service level management. It also provides the infrastructure that supports availability, data sharing, and response time. This book will be useful for IT professionals seeking to implement Cluster 1600 mission-critical solutions to address business intelligence applications, server consolidation, and collaborative computing.
Includes bibliographical references and index. - Print version record
Keywords: Parallel computers; IBM RISC System/6000 computers; File organization (Computer science); Ordinateurs parallèles; IBM RISC System/6000 (Ordinateur); Fichiers (Informatique); Organisation